Enhancing antimicrobial properties of fly ash mortars specimens through nanophase modification. (2016) - Vishwakarma, Vinita; Sudha, U.; Ramachandran, D.; Anandkumar, B.; George, R.P.; Kumari, Kalpana; Preetha, R.; Kamachi Mudali, U.; Pillai, C.S.
Abstract: Three different types of nanophase modified fly ash mortar specimens were prepared to evaluate the antimicrobial properties in seawater. Two percentage of OPC was replaced by 50-80nm and 50-70nm sized TiO2 (FAT) and CaCO3 (FAC) nanoparticles respectively. In the third type of mortar specimens a 2% of the OPC was replaced by mixture of both nanoparticles in same ratio (FATC). All the nanophase modified specimens along with FA specimens were cured in water for 28 days and exposed in seawater for a month. Specimens were withdrawn at different intervals for post-exposure analysis. Detailed microbiological characterization involving density of total heterotrophic aerobic bacteria, slime formers, anaerobic bacteria, manganese-oxidizing bacteria, fungus, sulfur oxidizing bacteria and biofilm imaging using epifluorescence microscopy, total dissolved and suspended solids in biofilm were carried out. pH reduction of the surface of the specimens were measured by flat surface electrode. Results demonstrated lesser pH reduction and enhanced antibacterial activity on the surface of FAT and FATC mortar specimens under the influence of TiO2 nanoparticles.